Bioeconomy Growth in Latvia. System-dynamics Model for High-value Added Products in Fisheries. (May 2017) - Runge, Kristine; Blumberga, Andra; Blumberga, Dagnija
Abstract: The rising environmental issues require higher bioeconomy impact on all sectors. In Latvia as well bioeconomy is starting to play a role in economic growth. The main challenge is to invent a new technology, which can provide sustainability and be economically justified. The target was to investigate how much profit you gain from high-value added products. In this study a system dynamics model was created for 5 high value added products: sunscreen, protein cocktail, skin regeneration cream, glue and facial cream. The main raw material for all products was retrieved from carp waste. The model created allows you to analyze the chosen production technology and its economic benefits. Profit of production depends on the price of the product, demand, production cost and capacity. The results show that the highest economical potential is in the cosmetics industry.